Wielki apetyt na „miniburgera”. O problemach opracowania komiksów w formacie MARC 21 - Szczecińska, Agnieszka; Kowalska, Anna (My University, 2010)
Od 2007 roku Biblioteka Uniwersytecka w Poznaniu gromadzi komiksy oraz materiały ich dotyczące. Momentem znaczącym dla gromadzenia tych wydawnictw był zakup prywatnej kolekcji 4670 komiksów. Niniejszy artykuł definiuje pojęcie „komiks” oraz omawia trudności, jakie napotykają katalogerzy w opracowaniu formalnym tego trudnego materiału. Autorki porównały rozwiązania zastosowane w innych bibliotekach. Przedstawiły również stan prac nad katalogowaniem komiksów w Bibliotece Uniwersyteckiej w Poznaniu. Artykuł zawiera przykłady i propozycje konkretnych rozwiązań.

Poznań University Library has been collecting comic books and other relevant material since 2007. A conducive opportunity for the decision to collect comics publications was a purchase of a private collection of 4,670 comic books the very same year. The present article introduces the reader to the notion of “comic book” or “comics” and discusses problems in formal processing that face cataloguers of this difficult material. The authors compare different solutions to the problem applied in other libraries and present the current state of affairs in comics cataloguing at Poznań University Library. The article is complemented with specific examples and particular solutions to be applied in the near future.
A lust for a “miniburger”. On problems encountered during library processing of comic books in MARC 21 format
Keywords: comic book; cataloguing; komiksy; katalogowanie